A prospective study predicting the outcome of chronic low back pain and physical therapy: the role of fear-avoidance beliefs and extraspinal pain - Feitosa,Aloma S.A. (2016)
ABSTRACT Objective: To identify the prognostic factors for conventional physical therapy in patients with chronic low back pain (CLBP). Methods: Prospective observational study. Participants: One hundred thirteen patients with CLBP selected at the Spinal Disease Outpatient Clinic. Main outcome measures: Pain intensity was scored using the Numeric Rating Scale (NRS), and function was measured using the Roland-Morris Disability Questionnaire (RMDQ). Results: The Fear-Avoidance Beliefs Questionnaire work subscale results (FABQ-work; odds ratio [OR] = 0.27, 95% confidence interval [CI] 0.13–0.56, p < 0.001) and extraspinal pain (OR = 0.35, 95% CI 0.17–0.74, p = 0.006) were independently associated with a decreased response to conventional physical therapy for CLBP. Conclusion: We identified high FABQ-work and extraspinal pain scores as key determinants of a worse response to physical therapy among CLBP patients, supporting the need for a special rehabilitation program for this subgroup.